Penanaman Sikap Cinta Tanah Air Dalam KegiatanEkstrakurikuler Pramuka Di Dabin 5 Uptd PendidikanKecamatan Wirosari Kabupaten Grobogan - PRIYOUTOMO, SUNU DWI, Prof. Dr. Abdul Ngalim, M.M, M.Hum, Dr.Suyatmini,SE.,M.Si (2016)
Sunu Dwi Priyo Utomo . Q.100140091 . Planting attitude Homeland Love In Extracurricular Activities Scouts in Dabin 5 UPTD Wirosari Subdistrict Grobogan . Prof.Dr.Abdul Ngalim , M.M , M.Hum Dr.Suyatmini , S.E , M.Si.Tesis.Pascasarjana Muhammadiyah University of Surakarta . 2016 . Indonesian people, especially young people , many are oblivious to the self-identity as a nation of Indonesia , because of his lifestyle tend to imitate the western culture that the world community is considered as a mecca . One reality is young people more interested in the products abroad. The influence of western lifestyle will slowly erode the sense of nationalism younger generation . Westernization real continues to erode the younger generation Indonesian nationalism . Such conditions are certainly very worrying . The purpose of this study is 1) to describe the attitude of patriotism planting in extracurricular activities scouts on Proficiency Requirements Unum ( SKU ) in Dabin 5 UPTD Wirosari Subdistrict Grobogan . 2 ) describe the cultivation of the attitude of patriotism in extracurricular activities scouts to Terms Specific Skills ( SKK ) in Dabin 5 UPTD Wirosari Subdistrict Grobogan . Data collection techniques using observation , interviews and documentation . Data analysis technique performed with data collection , data reduction , data presentation , and conclusion . Test the validity of the data in this study using triangulation sources. The results of this study were 1) Education Scouting as an extracurricular activity in Dabin 5 UPTD Wirosari Subdistrict Grobogan is the responsibility of the principal to the teachers as coaches Scout executive .. 2) Extracurricular activities guided by the General Proficiency Requirements (SKU) and Requirements Specific Skills (SKU ) .3) Habituation unpatriotic attitude on SKUs which are able to memorize at least three daily prayers, prayers can carry, can maintain the cleanliness of the room school, or place of worship, is able to help someone in the vicinity, following the flag ceremony with wisdom. Exemplary attitude of patriotism on the SKU of them are able to use Indonesian well and correctly, not littering, can show true deference to the Red and White Flag, and can be memorized to sing the national anthem Indonesia Raya. Application of the attitude of patriotism in them is SKK SKK singer, conductor SKK, SKK Cook, P3K SKK, SKK Explorer / Searching for Traces, SKK Camping, SKK Gardens and SKK greening. Keywords: patriotism, extracurricular, planting, scout.